Risks and benefits of screening for dementia in primary care: the IU CHOICE trial - Fowler, Nicole R. (J Am Geriatr Soc, 2019)
BACKGROUND/OBJECTIVE: The benefits and harms of screening of Alzheimer’ disease and related dementias (ADRD) are unknown. This study addressed the question of whether the benefits outweigh the harms of screening for ADRD among older adults in primary care. DESIGN, SETTING AND PARTICIPANTS: Single-blinded, 2-arm, randomized controlled trial (October 2012-September 2016) in urban, suburban, and rural primary care settings in Indiana. 4,005 primary care patients (≥65 years) were randomized to ADRD screening (n=2,008) or control (n=1,997). INTERVENTION: Patients were screened using the Memory Impairment Screen or the Mini-Cog™ and referred for a voluntary follow-up diagnostic assessment if they screened positive on either or both screening tests. MEASUREMENTS: Primary measures were health-related quality of life (Health Utilities Index (HUI)) at 12 months, depressive symptoms (Patient Health Questionnaire-9 (PHQ-9)), and anxiety symptoms (Generalized Anxiety Disorder 7-item scale (GAD-7)) at 1 month. RESULTS: The mean age was 74.2 years (standard deviation 6.9); 2,257 (66%) were female and 2,301 (67%) were white. At 12 months, we were unable to detect differences in health-related quality of life between the groups (effect Size (ES)= 0.009 [95% CI=−0.063, 0.080], p=0.81). At one month, differences in mean depressive symptoms (mean difference=−0.23 [90% CI= −0.42,−0.039]) and anxiety symptoms (mean difference=−0.087 [90% CI=−0.246, 0.072]) were within pre-specified equivalency range. Scores for depressive and anxiety symptoms were similar between the groups at all time points. No differences in healthcare utilization, advance care planning, and ADRD recognition by physicians were detected at 12 months. CONCLUSION: We were unable to detect a difference in health-related quality of life for screening for ADRD among older adults. We found no harm from screening measured by symptoms of depression or anxiety. Missing data, low rates of dementia detection, and high rate of refusal for follow-up diagnostic assessments after a positive screen may explain these findings. TRIAL REGISTRATION: ClinicalTrials.gov Identifier NCT01699503